Holy cow [compact disc, unabridged] - Duchovny, David (Macmillan Audio, 2015)
Elsie Bovary is a cow, and a pretty happy one at that-her long, lazy days are spent eating, napping, and chatting with her best friend, Mallory. One night, Elsie and Mallory sneak out of their pasture; but while Mallory is interested in flirting with the neighboring bulls, Elsie finds herself drawn to the farmhouse.